A Meta-Analysis of Statin Use and Risk of Hepatocellular Carcinoma. (20th March 2022) - Wang, Yikai; Wang, Wenjun; Wang, Muqi; Shi, Juanjuan; Jia, Xiaoli; Dang, Shuangsuo
Abstract : Background . The use of statins is a potential protective factor against the development of hepatocellular carcinoma. Therefore, we conducted a meta-analysis to evaluate the contribution of statins to the risk of hepatocellular carcinoma. Methods . We searched for PubMed and EMBASE through January 2021. Results . Thirty-two studies (eighteen cohort, eleven case-control, and three randomized controlled trials) reporting 56, 838 cases of hepatocellular carcinoma in 4, 963, 518 persons were included. Statin users were less likely to develop hepatocellular carcinoma than nonusers (adjusted odds ratio, 0.58; 95% CI: 0.51–0.67). Stratified analysis showed that statins reduced the risk of hepatocellular carcinoma in Asian and Western populations (odds ratio, 0.54 vs. 0.60). Besides, statins have protective effects against hepatocellular carcinoma after hepatitis B virus (odds ratio, 0.44; 95% CI: 0.22–0.85) and hepatitis C virus infections (odds ratio, 0.53; 95% CI: 0.49–0.57). Statins have protective effects on people with chronic liver disease (odds ratio, 0.52; 95% CI: 0.40–0.68) and on the general population (odds ratio, 0.60; 95% CI: 0.50–0.72). Lipophilic statins can prevent hepatocellular carcinoma (odds ratio, 0.51, 95% CI: 0.46–0.57), while hydrophilic statins cannot (odds ratio, 0.77, 95% CI: 0.58–1.02). The single-drug analyses showed that simvastatin (odds ratio, 0.53, 95% CI: 0.48–0.59), atorvastatin (odds ratio, 0.54, 95% CI: 0.45–0.64), rosuvastatin (odds ratio, 0.55, 95% CI: 0.37–0.83), lovastatin (odds ratio, 0.30, 95% CI: 0.15–0.62), and pitavastatin (odds ratio, 0.36, 95% CI: 0.17–0.75) had significant benefits. Further studies have shown that those in the high-dose group experienced better effects in preventing hepatocellular carcinoma (adjusted hazard ratio, 0.38 vs. 0.55). Further research found that the combined use of aspirin did not increase the chemoprevention effect of liver cancer (odds ratio, 0.57; 95% CI: 0.40–0.81). In addition, the preventive effect of statins improved with the extension of follow-up time (odds ratio, 0.54 vs. 0.65). Conclusion . Our meta-analysis shows that the use of statins is associated with a lower risk of liver cancer.